(untitled) (International journal of artificial intelligence, 2025)
This article covers the essence of the discipline of defectology, current issues in working with children with special educational needs, the role of this field in the modern education system, and areas for improvement. The main areas of defectology - surdopedagogy, typhlopedagogy, logopedagogy, and oligophrenopedagogy - are in the center of special attention. The author analyzes existing problems and gives specific proposals and recommendations for their elimination.